Efficacy of Duloxetine on electrodiagnostic findings of Paclitaxel-induced peripheral neuropathy, does it have a prophylactic effect? A randomized clinical trial - Aghabozorgi, Reza; Hesam, Marzieh; Zahed, Ghazal; Babaee, Marzieh; Hashemi, Mahdis; Rayegani, Seyed Mansoor (Anti-cancer drugs, 2023)
This study aimed to evaluate the efficacy of Duloxetine on electrodiagnostic findings of Paclitaxel-induced peripheral neuropathy in patients with breast cancer. This randomized, double-blind clinical trial was conducted on 40 patients with breast cancer who received Paclitaxel as their first chemotherapy session. All the patients were randomly allocated into two groups, intervention (20 subjects) and placebo (20 subjects). The intervention group received 30 mg duloxetine/day in the first week, followed by 60 mg (twice daily) until 8 weeks. The patient neurotoxicity questionnaire (PNQ) was used to evaluate the severity of neuropathy. Nerve conduction study was also performed. The evaluations were performed at the baseline and 8 weeks after the treatment. Out of 20 subjects in the placebo group, 10 (50%) patients had neurotoxicity (two milds, three moderate, four severe, and one incapacitated), according to PNQ. However, in the duloxetine group, two patients had mild neurotoxicity ( P = 0.03). Significant differences between groups related to the mean of Median Sensory Latency ( P <0.001), Median Motor Latency ( P < 0.001), and Median Motor velocity ( P = 0.001) were reported. However, the relative risk of polyneuropathy between the two groups (relative risk: 1) was not significant. Regarding the results, duloxetine could be an effective treatment for preventing paclitaxel-induced peripheral neuropathy in patients with breast cancer, and an electrodiagnostic study confirmed this effect.